Perspektif Mahasiswa Terhadap Peningkatan Ketahanan Nasional Melalui Pembelian Alusista Bekas - Dedi Kurniawan; Sigih Ardiansyah; Nelly Ertiani Simalango (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
State resilience has become a topic that is widely discussed and the state continues to try to maintain it through many strategic steps, regulations that strengthen its position and the procurement of new and used military equipment that further strengthens the state's defense position. Purchasing used defense equipment has become an increasingly attractive strategy for the Ministry of Defense to strengthen its military strength by taking advantage of its limited budget. This research aims to analyze the process of purchasing used defense equipment by the Ministry of Defense, as well as the factors that influence purchasing decisions. A case study approach is used by exploring data from various sources. The research results show that factors such as the condition of used defense equipment, reliability, military operational needs, as well as financial and information security aspects play an important role in the procurement process. Apart from that, transparency, accountability and compliance with regulations are also a focus in this process. The implication of this research is the importance of targeted policies to increase effectiveness and efficiency.